Notes on the Operation of Two Types of Aquatic Remotely Operated Vehicles Used During a Mock Turtle Survey. - Diefenbacher, Eric (Journal of North American Herpetology, 2022)
Aquatic remotely operated vehicles (ROV) show merit in providing in situ observations of sea turtles and freshwater turtles. However, turtles must be spotted above the water surface first then an ROV deployed for underwater observation. None have been used as a tool to survey for turtles solely under the water surface without direct observation first. Here we report on observations of two types of aquatic ROVs used during a mock turtle survey to determine the potential of freshwater turtles being found under the water surface without being directly observed first and if accurate species identification could be done.